Enhanced removal of fluoride from simulated groundwater by hydrochloric acid activated natural sepiolite nanofibers. Issue 14 (30th November 2021) - Zhang, Mengjia; Ma, Lili; Han, Xuan; Gao, Yuwei; Zhang, Yong; Han, Ruiming; Li, Shiyin; Wei, Wei; Zhang, Yong
Abstract: In this work, natural sepiolite (SEP) was disaggregated and activated by hydrochloric acid to obtain a novel adsorbent with a great potential for defluoridation of groundwater. The adsorbent was characterized by the phase composition, morphology, and structure using X-ray diffraction (XRD), Scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), and nitrogen adsorption measurement. Batch adsorption studies were performed as a function of pH, adsorbent dosage, contact time, initial fluoride concentration, and temperature. Results showed that hydrochloric acid activation could efficiently break the dense bundles and disaggregate the natural SEP fibers. The enhancement of fluoride adsorption could be attributed to the enhancement of BET surface area and the abundant hydroxyl groups of activated SEP nanofibers. The adsorption of fluoride on activated SEP followed pseudo-second-order kinetics and was well described by the Langmuir and Sips equilibrium model. The estimated fluoride adsorption capacity was approximately 303.5–328.8 mg/g at 283–313 K, which was much higher than that of previously reported adsorbents. This study indicated that the activated SEP nanofibers could be a promising material for treatment of groundwater containing fluoride. Graphical Abstract: Abstract : UF0001